Pengaruh Cash Holding dan Profitabilitas terhadap Perataan Laba dengan Reputasi Auditor sebagai Variabel Moderasi - Zahra Rifalda; Tresno Eka Jaya R; Rida Prihatni (Pusat Riset dan Inovasi Nasional, 2025)
The purpose of this research is to look at how auditor reputation acts as a moderator between cash on hand, profitability, and income smoothing. For this study, we used quantitative research strategy based on secondary data collected from the financial reports of banking sub-sector firms listed on the IDX between 2020 and 2023. You may find these reports on the IDX website or the linked company's website. The researcher used the purposive sampling approach to choose the sample based on predetermined criteria. The total number of observations for the 2020–2023 period was 124, and 47 firms were including in the final sample. Logistic regression analysis and moderated regression analysis were utilised to analyse the data, with the assistance of the SPSS program, version 26. The results of the study's hypothesis testing show that auditor reputation has no effect on income smoothing, profitability has no effect on income smoothing, cash holding has no effect on income smoothing, auditor reputation is able to minimise the effect of cash holding on income smoothing, auditor reputation is able to minimise the effect of profitability on income smoothing.